2017
DOI: 10.1039/c7ob00283a
|View full text |Cite
|
Sign up to set email alerts
|

The application of perfluoroheteroaromatic reagents in the preparation of modified peptide systems

Abstract: The perfluoroheteroaromatic reagent pentafluoropyridine has proved to be a highly reactive electrophile, undergoing SAr arylation reactions in the presence of a range of nucleophilic peptide side chains (i.e. cysteine, tyrosine, serine and lysine) under mild conditions. Moreover, we have shown how one-step peptide-modification using perfluoroheteroaromatics can deliver enhanced proteolytic stability in pharmaceutically-relevant peptides such as oxytocin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 33 publications
5
40
0
2
Order By: Relevance
“…[249] It is also possible to discover new ligands for copper-orpalladiumcatalyzed arylation reactions that form C(sp 2 )ÀOb onds (for Ser,T hr, and Ty r) and C(sp 2 )-N(sp 2 )( for His) bonds on proteins.A nother strategy is to utilize protein environments and recognition elements to promote otherwise difficult arylation chemistry,a sd emonstrated in Ballsm ethod for arylation of amides in protein backbones. [249] It is also possible to discover new ligands for copper-orpalladiumcatalyzed arylation reactions that form C(sp 2 )ÀOb onds (for Ser,T hr, and Ty r) and C(sp 2 )-N(sp 2 )( for His) bonds on proteins.A nother strategy is to utilize protein environments and recognition elements to promote otherwise difficult arylation chemistry,a sd emonstrated in Ballsm ethod for arylation of amides in protein backbones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[249] It is also possible to discover new ligands for copper-orpalladiumcatalyzed arylation reactions that form C(sp 2 )ÀOb onds (for Ser,T hr, and Ty r) and C(sp 2 )-N(sp 2 )( for His) bonds on proteins.A nother strategy is to utilize protein environments and recognition elements to promote otherwise difficult arylation chemistry,a sd emonstrated in Ballsm ethod for arylation of amides in protein backbones. [249] It is also possible to discover new ligands for copper-orpalladiumcatalyzed arylation reactions that form C(sp 2 )ÀOb onds (for Ser,T hr, and Ty r) and C(sp 2 )-N(sp 2 )( for His) bonds on proteins.A nother strategy is to utilize protein environments and recognition elements to promote otherwise difficult arylation chemistry,a sd emonstrated in Ballsm ethod for arylation of amides in protein backbones.…”
Section: Discussionmentioning
confidence: 99%
“…Arylation reactions are desired for natural amino acid residues,o ther than lysine and cysteine.T argeting other nitrogen-and oxygen-based nucleophiles (e.g., His,S er,T hr, and Ty r) is highly valuable and promising for generating structurally diverse protein conjugates.Such nucleophiles are, in most cases,m uch less reactive compared to the cysteine thiol group or the lysine e-amine,p resenting significant challenges for developing arylation chemistry targeting these sites.O ne strategy is to tune the reactivity and selectivity of S N Ar arylation reactions by changing the electronic and steric properties of the arylation reagents,a s demonstrated by recent reports on arylation of residues other than cysteine using perfluoroheteroaromatic reagents. [249] It is also possible to discover new ligands for copper-orpalladiumcatalyzed arylation reactions that form C(sp 2 )ÀOb onds (for Ser,T hr, and Ty r) and C(sp 2 )-N(sp 2 )( for His) bonds on proteins.A nother strategy is to utilize protein environments and recognition elements to promote otherwise difficult arylation chemistry,a sd emonstrated in Ballsm ethod for arylation of amides in protein backbones. [191] Notably,C hen and Liu recently developed an intramolecular palladiumcatalyzed C(sp 3 )-H arylation strategy for the synthesis of peptide macrocycles,which provided apotential approach for the modification of aliphatic chains in amino acid residues.…”
Section: Discussionmentioning
confidence: 99%
“…[249] Andererseits besteht die Mçglichkeit, neue Liganden fürK upfer-o der Palladium-katalysierte Arylierungen zu entwickeln, mit deren Hilfe C(sp 2 )-O-Bindungen (fürSer,Thr und Ty r) bzw.C(sp 2 )-N(sp 2 )-Bindungen (fürHis) an Proteinen geknüpft werden kçnnen. Kupp-lungsreaktionen fürandere Stickstoff-und Sauerstoff-haltige Nukleophile (d.h. die Reste von His,S er,T hr und Tyr) sind von besonderem Wert fürd ie Herstellung strukturell vielfältiger Proteinkonjugate.D ad iese Nukleophile im Allgemeinen weitaus weniger reaktiv sind als die Thiolgruppe in Cystein oder die e-Aminogruppe in Lysin, ergeben sich besondere Herausforderungen fürs peziell auf diese Gruppen ausgerichtete Arylierungsreaktionen.D ies kçnnte einerseits durch eine Anpassung der Reaktivitätu nd Selektivitätv on S N Ar-Arylierungen erreicht werden, indem die elektronischen und sterischen Anforderungen der Arylierungsreagentien verändert werden, wie in jüngeren Arbeiten zur Arylierung anderer Reste als Cystein mit Perfluorheteroarenen gezeigt wurde.…”
Section: Zusammenfassung Und Ausblickunclassified
“…Kupp-lungsreaktionen fürandere Stickstoff-und Sauerstoff-haltige Nukleophile (d.h. die Reste von His,S er,T hr und Tyr) sind von besonderem Wert fürd ie Herstellung strukturell vielfältiger Proteinkonjugate.D ad iese Nukleophile im Allgemeinen weitaus weniger reaktiv sind als die Thiolgruppe in Cystein oder die e-Aminogruppe in Lysin, ergeben sich besondere Herausforderungen fürs peziell auf diese Gruppen ausgerichtete Arylierungsreaktionen.D ies kçnnte einerseits durch eine Anpassung der Reaktivitätu nd Selektivitätv on S N Ar-Arylierungen erreicht werden, indem die elektronischen und sterischen Anforderungen der Arylierungsreagentien verändert werden, wie in jüngeren Arbeiten zur Arylierung anderer Reste als Cystein mit Perfluorheteroarenen gezeigt wurde. [249] Andererseits besteht die Mçglichkeit, neue Liganden fürK upfer-o der Palladium-katalysierte Arylierungen zu entwickeln, mit deren Hilfe C(sp 2 )-O-Bindungen (fürSer,Thr und Ty r) bzw.C(sp 2 )-N(sp 2 )-Bindungen (fürHis) an Proteinen geknüpft werden kçnnen. Eine weitere Strategie besteht darin, Proteinumgebungen und Erkennungselemente zu nutzen, um anderweitig schwierig umsetzbare Arylierungen durchzuführen, wie die von Ball und Mitarbeitern vorgestellte Methode fürdie Arylierung von Amidbindungen in Proteingerüsten.…”
Section: Zusammenfassung Und Ausblickunclassified
“…[2] Thes ame group showed that decafluorodiphenyl sulfone (2)r eacts with diamine-bearing peptides to afford 4,4'-diamino octafluorodiphenyl sulfone bridged macrocycles. [3][4][5] In our own studies on constrained peptidomimetics,w e were considering ways to build bridged bicyclic structures by transannulating existing macrocycles. [6] Thee ase of fluoride ipso substitutions was appealing.H owever,r elative to reagents 1 and 2,wesought broader nucleophile participation and product geometries that are more compatible with smaller polyheterocyclic structures.R ather than aromatic substitutions,w ec hoose to examine vinylic substitutions of fluoride from octafluorocyclopentene (OFCP, 3; Figure 1).…”
mentioning
confidence: 99%